Proteomics as a tool to improve investigation of substantial equivalence in genetically modified organisms: The case of a virus-resistant tomato - Corpillo, Davide; Gardini, Giulia; Vaira, Anna Maria; Basso, Manuela; Aime, Silvio; Accotto, Gian Paolo; Fasano, Mauro (Proteomics (Weinheim), 2004)
At present, the so‐called “substantial equivalence” is the only widely accepted criterion for deciding whether or not a transgenic food is, from an alimentary point of view, to be considered totally correspondent to the “traditional” one from which it derives. Although never exactly defined, it deals with a comparison between the chemical composition of the two foods. A more in‐depth analysis can be performed by one of the most suitable methods that allows for the simultaneous screening of many components without prior identification, the analysis of the proteome. As a model for testing this kind of approach, we compared protein expression of two types of tomato plants, having the same genetic background, except for a virus resistance trait introduced by genetic engineering. When proteins extracted from seedlings of the two types were analyzed by two‐dimensional electrophoresis, no significant differences, either qualitative or quantitative, were detected, indicating that in this case the expression of major proteins was unmodified by the genetic manipulation. Fifteen proteins were identified by peptide mass fingerprinting.